Los modificadores verbales; concepto y clasificación desde un modelo revisado de valencia lógico-semántica - Albi Aparicio, Miguel (Studia Romanica Posnaniensia, 2004)
In this article a possible definition and classification of the verbal modifiers is proposed. The theoretical frame is the Valence Theory complemented with aspects from cognitive linguistics inspired by the 2-Level-Semantics. The classification is done on the basis of verbal semantics focussing on which entities are modified.